Two Scaffolds from Two Flips: (α,β)/(β,γ) CH(2)/NH “Met-Im” Analogues of dTTP - Kadina, Anastasia P. (Org Lett, 2015)
Novel α,β-CH(2) and β,γ-NH (1a) or α,β-NH and β,γ-CH(2) (1b) “Met-Im” dTTPs were synthesized via monodemethylation of triethyl-dimethyl phosphorimido-bisphosphonate synthons (4a, 4b), formed via a base-induced [1,3]-rearrangement of precursors (3a, 3b) in a reaction with dimethyl or diethyl phosphochloridate. Anomerization during final bromotrimethylsilane (BTMS) deprotection after Mitsunobu conjugation with dT was avoided by microwave conditions. 1a was 9-fold more potent in inhibiting DNA polymerase β, attributed to an NH-group interaction with R183 in the active site. [Image: see text]